Wear Resistances of X6Cr17 Ferritic Stainless-Steel Surfaces Coated with Al2O3 Powders Using Thermal Spray Method - Durmuş, Hülya; Turkmen, Mustafa; Çalıgülü, Ugur (My University, 2020)
The aim of this study was to improve the surface properties of the X6Cr17 ferritic stainless steels bycoating with the Al2O3-TiO2 powders in the thickness of 0-100µm, 100-200µm and 200-300µm by usingthe plasma spray method, one of thermal spray methods. Wear resistance of the samples was investigatedafter the coating process. The tests were carried out by pin-on-disc method according to ASTM G133standard. After examination of the results, it was observed highest abrasion resistance of A3 sample. Itwas concluded that the abrasion resistance in the high hardness sample does not mean that it will be gooddue to the high hardness.
Keywords: Mühendislik; Makine; Malzeme Bilimleri; Özellik ve Test